High-dimensional assessment of B-cell responses to quadrivalent meningococcal conjugate and plain polysaccharide vaccine. Issue 1 (December 2017) - O'Connor, Daniel; Clutterbuck, Elizabeth; Thompson, Amber; Snape, Matthew; Ramasamy, Maheshi; Kelly, Dominic; Pollard, Andrew
Abstract Background Neisseria meningitidis is a globally important cause of meningitis and septicaemia. Twelve capsular groups of meningococci are known, and quadrivalent vaccines against four of these (A, C, W and Y) are available as plain-polysaccharide and protein-polysaccharide conjugate vaccines. Here we apply contemporary methods to describe B-cell responses to meningococcal polysaccharide and conjugate vaccines. Methods Twenty adults were randomly assigned to receive either a meningococcal plain-polysaccharide or conjugate vaccine; one month later all received the conjugate vaccine. Blood samples were taken pre-vaccination and 7, 21 and 28 days after vaccination; B-cell responses were assessed by ELISpot, serum bactericidal assay, flow cytometry and gene expression microarray. Results Seven days after an initial dose of either vaccine, a gene expression signature characteristic of plasmablasts was detectable. The frequency of newly generated plasma cells (CXCR3+ HLA-DR+ ) and the expression of transcripts derived fromIGKC andIGHG2 correlated with immunogenicity. Notably, using an independent dataset, the expression of glucosamine (N-acetyl)-6-sulfatase was found to reproducibly correlate with the magnitude of immune response. Transcriptomic and flow cytometric data revealed depletion of switched memory B cells following plain-polysaccharide vaccine. Conclusions These data describe distinct gene signatures associated with the production of high-avidity antibody and a plain-polysaccharide-specific signature, possibly linked to polysaccharide-induced hyporesponsiveness.